The Role of AUKUS in Australia’s Military Capacity Building Strategy - Lia Aulia Lubis; Anak Agung Banyu Perwita; Rizerius Eko Hadisancoko (International Journal of Society and Law, 2024)
This study examines the role of AUKUS in enhancing Australia's military capacity within the context of the evolving geopolitical in the Indo-Pacific region. The trilateral security partnership between Australia, the United Kingdom, and the United States, known as AUKUS, was established to increase Australia's defense capabilities, focusing on the development of nuclear-powered submarines, cyber security, artificial intelligence, and underwater warfare technologies. The analysis highlights how AUKUS addresses Australia's pre-existing military challenges by providing advanced technology and strategic support. The SSN-AUKUS submarines, integrating cutting-edge technology from all three nations, represent a significant advancement in Australia's naval capabilities. The partnership also emphasizes economic and social benefits, including job creation and infrastructure development. However, the study also considers potential drawbacks, such as increased regional tensions and the risks of an arms race. The findings underline AUKUS's critical impact on Australia's ability to maintain regional security and stability in the South China Sea, while also noting the necessity for balanced diplomatic efforts to mitigate adverse effects.Keywords:Australia, AUKUS, SSN-AUKUS, military capacity, South China Sea